The language of the gods in the world of men : Sanskrit, culture, and power in premodern India - Pollock, Sheldon I. (ACLS Fellows' Publications., 2006)
Exploring the rise and fall of Sanskrit as a vehicle of poetry and polity, this title traces the two great moments of its transformation. Drawing parallels with the rise of Latin literature and the Roman empire, it asks whether these very different histories challenge theories of culture and power and suggest possibilities for practice.